Case Study: Living Smart in Australian Households: Sustainability Coaching as an Effective Large-Scale Behaviour Change Strategy - Ashton-Graham, C.; Newman, Peter (Edward Elgar, 2013)
This case study presents the methods, results and learnings from an innovative and large-scale behaviour change programme addressing, in a holistic manner, the major contributors to the carbon footprint of households. The Living Smart Households project was developed by the Department of Transport in Western Australia to build upon successful behavioural interventions in small group sustainability and large-scale transport and water demand management. Two large-scale demonstration projects have been completed, across 25 000 households, testing different strategies and techniques both within and between projects. Each project had a budget of around $AUS 2 million and was delivered (research, service delivery and evaluation) over a two-year period. The Living Smart Households project provides a best practice example of programme design that is based on research insights, connected to formative research in the target community and monitored and evaluated across process, output and outcome measures. The successes of the Living Smart Households project include strong market penetration (engaging with around 60 per cent of target households), large-scale operation (managed across more than 10 000 households), significant behaviour change (households adopting conservation behaviours such as short showers, switching off standby power loads and installing solar electric panels) and independently verified outcomes (around a 6 per cent reduction in energy, water and car use across programme participants compared to control).